Evaluation of Retention Force of Polyetheretherketone (PEEK) and Cast Cobalt-Chromium Circumferential Clasps: A comparative study - Hussein T. Abed; Aliaa W. Al-Omari (University of Mosul, College of Dentistry, 2022)
Aims: The aim of this in-vitro study was to compare the retention force of Polyetheretherketone (PEEK) and Cobalt-Chromium (Co-Cr) clasps by mechanical cycling test simulating ten years of use. Materials and Methods: 72 clasps samples were fabricated on a standardized e-max upper right first premolar, it is divided into 24 Co-Cr clasps, and 48 PEEK clasps which were subdivided into 24 clasps (2.4mm width), and 24 clasps (3.00mm width).Each group was further subdivided (n=8 clasps) into amounts of abutment undercut 0.25mm, 0.50, and 0.75mm undercuts. Mechanical cycling of each clasp was performed for 15000 times on its specific abutment crown. The retention force of each clasp in newton was measured every 1500 cycles by applying a tensile force using a universal tensile machine. Results: The retention force of Co-Cr clasps was higher significantly than the PEEK clasps retention force for the three undercuts. Deeper undercut showed a significantly higher retention force for both materials. All subgroups (except 0.75mm Co-Cr group) exhibit an increase in retention force after first 1500 cycles followed by gradual decrease till the end of 15000 cycles. Conclusions: The retention force of PEEK clasps with both widths along 15000 cycles of insertion/removal were lower than Co-Cr clasps but still sufficient for clinical use at 050, and 0.75mm undercut but not enough at 0.25mm undercut.